Pre- and Postoperative Circulating IGF-I, IGFBP-3, and IGFBP-7 Levels in Relation to Endocrine Treatment and Breast Cancer Recurrence: A Nested Case-Control Study - Rosendahl, Ann H.; Björner, Sofie; Ygland Rödström, Maria; Jirström, Karin; Borgquist, Signe; Ingvar, Christian; Pollak, Michael N.; Jernström, Helena (Frontiers in Oncology, 2021)
Insulin-like growth factor-I (IGF-I) and its binding proteins (BPs) have been associated with breast cancer risk, especially high IGF-I concentrations and the biologically active fraction estimated as the IGF-I/IGFBP-3 molar ratio. The relation of circulating IGF-I and IGFBP-3 concentrations with risk of breast cancer recurrence has been less documented. In addition a new member to a sub-group of the IGFBP-superfamily was recently identified, the low affinity IGFBP-7. To date, the role of systemic IGFBP-7 in breast cancer progression has not been investigated. Our purpose was to establish whether circulating IGF-I, IGFBP-3, and IGFBP-7 levels are related to recurrence-risk in breast cancer. A case-control study was nested within the population-based BCBlood cohort of 853 breast cancer patients diagnosed 2002–2010 in Sweden and followed through 2012. In total, 95 patients with recurrence and 170 controls were matched on age and tumor characteristics. Plasma IGF analytes and tumor membrane IGF-I receptor (IGF-IRm) positivity were analyzed and recurrence-risk was evaluated with conditional logistic regression. Preoperative tertiles of IGF-I and IGFBP-3 were both positively associated with recurrence-risk, but not IGFBP-7. The trend was of borderline significance for IGF-I, T1:REF, T2 OR:1.6, T3 OR: 2.2 adjusted Ptrend=0.057 and significant for IGFBP-3 T1:REF, T2 OR:1.2, T3 OR: 2.1 adjusted Ptrend=0.042. The models were adjusted for age, anthropometric factors, smoking, and treatments. There was a significant interaction between IGFBP-7 and IGF-IRm positivity on recurrence, where the highest IGFBP-7 highest IGFBP-7 tertile conferred increased recurrence-risk in patients with IGF-IRm positive tumors but not in those with IGF-IRm negative tumors (Pinteraction=0.024). By the 1-year visit, age-adjusted IGF-I levels were reduced by 17% while IGFBP-3 and IGFBP-7 were stable. IGF-I levels were significantly reduced by radiotherapy in all patients and by tamoxifen in patients with ER+ tumors. Postoperative changes >10% (n=208) in IGF-I, IGFBP-3, IGFBP-7, or the IGF-I/IGFBP-3 ratio did not predict recurrence after adjustment for preoperative levels, age, anthropometric factors, smoking, and treatments. In conclusion, this study suggests that preoperative IGF-I and IGFBP-3 levels, but not postoperative changes, might provide independent prognostic information and influence breast cancer recurrence. The role of IGFBP-7 in breast cancer merits further study.